An Update on Foot and Ankle Fellowship Website Content and Accessibility. Issue 1 (30th March 2020) - Khwaja, Ansab; Du, Peter; Sherman, Nathan; Truchan, Lisa
Background: The content and accessibility of foot and ankle fellowship websites impact applicants and fellowship programs. This study aimed to evaluate the accessibility provided via the American Orthopaedic Foot & Ankle Society (AOFAS) websites and individual websites. Methods: The AOFAS website was used to identify existing foot and ankle fellowship programs. The database information was reviewed for links to fellowship program websites, which was corroborated through a Google search for accessibility. Information from fellowship program websites and the AOFAS was analyzed for the presence of recruitment and educational content, and this analysis was compared to previously reported metrics. Results: Forty-eight orthopedic foot and ankle fellowship programs were identified. The AOFAS database featured direct links to 19 (40%) fellowship websites with the Google search providing direct links to 35 (73%) websites. Foot and ankle fellowship information markedly improved in domains of Salary/Benefits (+233%), Rotations/Curriculum (+199%), and Faculty Listing (+67%), but there was a reduction in available content in the domains of Operative Experience (–79%), Office/Clinic information (–78%), and Didactics (–39%) compared with the lone existing study. Conclusion: There continues to be variability between foot and ankle fellowship websites and the AOFAS website regarding program content and descriptions. Some information is more readily available, but other domains have less information now than in previously reported research.